THE SOVEREIGNTY OF THE INDIVIDUAL PSYCHOLOGICAL SPACE IN SEMI- CLOSED LEARNING GROUP: PERSONAL AND GROUP FACTORS - Tarasov, S.V.; Drobysheva , T.V. (Modern Psychology, 2021)
The study examines the preservation of the psychological privacy of individuals in a semi-closed group as an indicator of their subjective qualities. The aim of the research was to identify the contribution of socio-psychological characteristics (personal and group) to the regression model of the sovereignty of psychological space in the group of students of military higher education. The results showed that the sovereignty of psychological space is due more to socio-psychological (values, motivation to enter and choose a profession in the future, perceptions of a group) than to group (group cohesion, sociometric status, group norms) characteristics.
Keywords: sovereignty of the individual psychological space; semi-closed learning group; relationship between individual and collective subject; specifics of socialization